Kaylee Congdon: capstone - Congdon, Kaylee, artist (Colorado State University. Libraries, 2024)
The artist's statement: My artistic journey is a personal exploration of girlhood and sibling dynamics. Drawing from my memories and emotions my work captures the genuine connection that shapes one's identity during the formative years. My work is inspired by images from my childhood where my sisters and I were in the midst of shared experiences evoking a sense of nostalgia and capturing the stillness in the moment. Utilizing oil on canvas and a palette of bright and playful colors I bring these memories to life. I enhance the nostalgia of the images by making bold gestural brushstrokes. The subject matter within my paintings carries layers of meaning that prompt viewers to reflect on their own experiences of growing up, fostering connection within my work. My art shows the transformative power of shared experiences, and sisterhood, while also portraying my personal memories. Through my work, I invite viewers to address the complexities of nostalgia and memory offering a glimpse into the joys, and cherished memories that shape us into who we are.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting